2009
DOI: 10.1007/978-1-60327-114-1_27
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Production of Sweet Peas (Lathyrus odoratus L.) via Axillary Shoots

Abstract: The genus Lathyrus is best known because it includes a number of wild relatives of the protein pea which, despite being generally neglected and under-utilised, hold considerable potential as a useful genetic resource for the acquisition of interesting stress resistant traits important for a sustainable agriculture. However, also included in this genus are important commercially produced species with a significant ornamental value, among which the sweet pea (Lathyrus odoratus L.). Surprisingly though, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Weber et al [ 39 ] used apical meristems explants of the interspecific hybrids originating from crosses between H. annuus and nine others species of Helianthus , and concluded that a species regeneration capacity was significantly determined by the individual genotype. Variability in the organogenic responses from the axillary buds among genotypes was observed in many other species including Rosa rugosa [ 72 ], Vigna unguiculata [ 73 ], and Lathyrus sativus [ 74 ]. The observed variation in the morphogenetic response among the six tested plants of H. verticillatus warrants future studies for the levels of endogenous PGRs in the context of genotype and stem localization.…”
Section: Resultsmentioning
confidence: 99%
“…Weber et al [ 39 ] used apical meristems explants of the interspecific hybrids originating from crosses between H. annuus and nine others species of Helianthus , and concluded that a species regeneration capacity was significantly determined by the individual genotype. Variability in the organogenic responses from the axillary buds among genotypes was observed in many other species including Rosa rugosa [ 72 ], Vigna unguiculata [ 73 ], and Lathyrus sativus [ 74 ]. The observed variation in the morphogenetic response among the six tested plants of H. verticillatus warrants future studies for the levels of endogenous PGRs in the context of genotype and stem localization.…”
Section: Resultsmentioning
confidence: 99%
“…Wesely et al (2010) observed that MS medium supplemented with 0.5 mg/l IBA resulted in 8.3 roots per shoot of Boerhaavia diffusa. Ochatt et al (2010) demonstrated that for rooting of Lathyrus odoratus L. microshoots, they are explanted onto medium with 0.5 to 1 mg/L NAA. Abido et al (2011) stated that the highest number of roots were obtained when Mirabilis jalapa neoformed shoots were treated with NAA at 0.2 mg/l.On the other side, Shah et al (2006) reported that the highest numbers of plants of Bougainvillea spectabilis were rooted when MS medium was supplemented with 2.5 mg/l IBA and NAA 2.5 mg/l.…”
Section: Resultsmentioning
confidence: 99%